Quality of Life Among Geriatric Population Living with Functional Disabilities in Urban Slum Dwellers of Kolkata, India - Aritraa Hazra; Sukanta Majumdar; Shuvankar Mukherjee; Avijit Paul; Nabanita Bhattacharyya (Medsci Publications, 2023)
Introduction: Population aging globally impacts individuals, families, communities, and societies. Longer life spans result in an increasing elderly population, leading to the 21st century being known as the century of the elderly. Disability, stemming from health conditions and surroundings, presents challenges necessitating interventions against environmental and social barriers. This study aims to examine the correlation between disability and quality of life (QOL) among elderly individuals living in Kolkata slums. Methodology: The observational study focused on the 100 geriatric populations in Dhapa slums using systematic random sampling. Data was collected using the Lawton Brody IADL Scale, and QOL assessment using WHOQOL-BREF. Results: Majority of the participants were male (64%) and from the general caste (63%). Disability prevalence was 28%. Better QOL scores were observed in males, younger age groups, married individuals and non-diabetics. The physical health domain had the highest QOL score. Literate individuals and those without hypertension or diabetes had higher QOL. Conclusion: India's aging population poses challenges for society and the economy. The study identified factors impacting disability and QOL in the elderly. Improving psychological care, awareness of government schemes, education, and targeted policies can enhance elderly quality of life.